DESIGN AND CONSTRUCTION OF FILLING CAPPING TOOLS BASED ON OUTSEAL PLC SUPPORT HMI - Qirom, Qirom; Fatah, Bagus Islahul; Rizal, Muhammad Khairul; Hanif, Rizki Abdul (Jurnal Disprotek, 2024)
The use of automatic Filling Capping is an essential requirement in increasing the efficiency of liquid production in bottles, which in turn speeds up the production process and reduces production costs. Even though large companies have adopted sophisticated industrial machines for this process, many small industries or Micro, Small and Medium Enterprises (MSMEs) still rely on direct human labor in production, limited by machine limitations or minimal automation. With rapid technological developments and more affordable costs, it is possible to create automatic bottle filling equipment that can support MSME production processes. This system is designed using Outseal PLC, where sensors as input will be processed through a ladder diagram program, producing output on relays which are then configured with actuators on the tool being made. The mechanical system of the tool is in accordance with the mechanical drawing design that has been prepared, consisting of a conveyor system, filling system, sleeding cup and capping system. In trials, control of the filling capping system was reliable via Outseal PLC. The tool's work process, from filling to capping, can be completed in around 14 seconds per 250 ml bottle.RANCANG BANGUN ALAT FILLING CAPPING BERBASIS OUTSEAL PLC SUPPORT HMIPenggunaan Filling Capping otomatis menjadi suatu kebutuhan esensial dalam meningkatkan efisiensi produksi cairan dalam botol, yang pada gilirannya mempercepat proses produksi dan mengurangi biaya produksi. Meskipun perusahaan besar telah mengadopsi mesin industri canggih untuk proses ini, industri kecil atau Usaha Mikro, Kecil, dan Menengah (UMKM) masih banyak yang mengandalkan tenaga manusia langsung dalam produksi, terbatas oleh keterbatasan mesin atau otomatisasi yang minim. Dengan perkembangan teknologi yang pesat dan biaya yang lebih terjangkau, memungkinkan pembuatan alat pengisian botol otomatis yang dapat mendukung proses produksi UMKM. Sistem ini dirancang dengan menggunakan Outseal PLC, di mana sensor sebagai input akan diolah melalui program ladder diagram, menghasilkan output pada relay yang kemudian dikonfigurasi dengan aktuator pada alat yang dibuat. Sistem mekanik alat sesuai dengan desain gambar mekanik yang telah disusun, terdiri dari sistem konveyor, sistem filling, sleeding cup, dan sistem capping. Proses kerja alat filling capping dapat diselesaikan dalam waktu sekitar 14 detik per botol berukuran 250 ml. Hasil pengujian komunikasi lancar antara HMI Modbus dengan PLC Outseal adalah 9 meter.